Strategi Komunikasi Partisipatif Pemerintahan Desa Dalam Pemberdayaan Masyarakat Perbatasan RI-PNG - Rery, Samdar; Mustofa, Hamim; Ahmad, Busyairi; Nahria, Nahria (JURNAL KOMUNIKATIO, 2024)
Mosso is a village located in between Indonesia - Papua New Guinea border. It is often known for its difficulty. In reaching government’s efforts to empower the community through the use of village funds can make a positive contribution to the progress of the Mosso Village community. So it is necessary to develop communication strategy to empower the community by utilizing of village fund allocation that can increase community participation. The theory used in studying the results of this research is the development communication theory. The methods used in this study are descriptive qualitative research and data analysis techniques using Miles and Huberman models, namely data collection, data reduction, data presentation, and conclusion drawing/verifying (verification). The results of this study show that the village government’s communication strategy has not been maximized in increasing community participation through utilizing empowerment programs, this is marked by 1). The communication that has occurred so far has been more monologic/directive in nature, communication has not led to a form of dialogue with the community, 2). The weak process of supporting the empowerment program consistently by the village government, starting from the planning, implementation, to evaluation stages.